Giant Taro (Alocasia macrorrhiza) Root Meal with or without Coconut Oil Slurry as Source of Dietary Energy for Laying Hens - Diarra, S.S.; Oikali, C.; Rasch, I.M.; Taro, L.; Vatigava, M.; Amosa, F. (Malaysian Journal of Animal Science, 2016)
The effect of feeding Alocasia macrorrhiza root meal (AMRM) with or without added coconut oil slurry (COS) on egg production and egg qualities was investigated in a 20-week experiment. A control diet based on maize and 4 other diets containing 10 and 20% AMRM with or without COS were fed each to 4 replicates of 10 birds in a completely randomized design. There were no significant dietary effects on feed intake (FI) and the intake of lysine, methionine and metabolizable energy (ME). Birds fed the 20% AMRM_COS added significantly less weight during the experimental period compared to the control fed group. Body weight change (BWC) did not differ among the AMRM fed birds. Per cent hen-day and feed conversion ratio were depressed on 20% AMRM and egg weight on 10% AMRM but these depressing effects were overcome by COS addition. Egg shape index, Haugh unit and per cent shell were not affected by the diet. It is concluded that AMRM can replace 10% dietary maize without adverse effect on laying performance but 20% replacement negatively impacts on hen-day and egg weight. These adverse effects are however, overcome by treating AMRM with COS at the ratio of 9: 1. More research into higher levels of COS treated AMRM in the diet is warranted.